2022
DOI: 10.1186/s12860-022-00442-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growth hormone/estrogen/androgen on COVID-19-type proinflammatory responses in normal human lung epithelial BEAS-2B cells

Abstract: Background COVID-19 is a disease caused by SARS-CoV-2, which can cause mild to serious infections in humans. We aimed to explore the effect of growth hormone (GH)/estrogen/androgen in normal human lung epithelial BEAS-2B cells on COVID-19-type proinflammatory responses. Methods A BEAS-2B COVID-19-like proinflammatory cell model was constructed. After that, the cells were treated with GH, 17β-estradiol (E2), and testosterone (Tes) for 24 h. CCK-8 as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In a clinical study of 456 patients, growth hormone and IGF-1 deficiency were found in COVID-19 cases with lung involvement, regardless of age or gender; COVID-19 infection progressed worse in GH and IGF-1 deficiency [ 151 ]. Another study examining COVID-19 inflammation in cellular model found that growth hormone and estradiol improved inflammation, but testosterone had the opposite effect [ 152 ]. However, a potential complicating factor of growth hormone treatment for COVID-19 is that acromegaly, a state of endogenous GH excess, results in myocardial hypertrophy and decreased cardiac performance with increased cardiovascular mortality [ 153 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical study of 456 patients, growth hormone and IGF-1 deficiency were found in COVID-19 cases with lung involvement, regardless of age or gender; COVID-19 infection progressed worse in GH and IGF-1 deficiency [ 151 ]. Another study examining COVID-19 inflammation in cellular model found that growth hormone and estradiol improved inflammation, but testosterone had the opposite effect [ 152 ]. However, a potential complicating factor of growth hormone treatment for COVID-19 is that acromegaly, a state of endogenous GH excess, results in myocardial hypertrophy and decreased cardiac performance with increased cardiovascular mortality [ 153 ].…”
Section: Discussionmentioning
confidence: 99%